Pemanfaatan Kitin Sebagai Bahan Membran Elektroda Enzim Diamin Oksidase Untuk Biosensor Histamin - Abdul Karim; Abd. Rauf Patong; Abd. Wahid Wahab; Indah Raya (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
This research aims to utilize isolated chitin from shrimp waste to develop histamine biosensors basedon diamine oxidase (DAO) enzyme electrode with cyclic voltammetry. DAO enzyme trapped in the chitin-cellulose acetate membranes with various comparisons were layered on the Pt electrode. Histamine will be oxidized by the DAO enzyme produces aldehydes and H2O2 which acts as an electron transfer mediator. Biosensor performance is influenced by several factors, especially the concentration and composition of electrode membranei.Comparison of chitin-cellulose acetate used in this study were 1:1, 2:1 and 3:1. Isolated chitin from the shrimp waste is chemically obtainedrendamen of 23.6%, and characterization of electrode membrane by FTIR and cyclic voltammetry showed that the DAO enzymes electrode with chitin-cellulose acetate membrane 2:1 is the best composition.